EVALUASI MILLENIUM DEVELOPMENT GOALS (MGDs) DALAM MENANGGULANGI KEMISKINAN DAN KELAPARAN MENUJU SUSTAINABLE DEVELOPMENT GOALS (SGDs) DI KOTA MEDAN - Dede Ruslan (Quantitative Economics Journal, 2016)
Program Millennium Development Goals (MDGs) have ended in 2015, Indonesia's commitment to achieve the MDGs is done by making the MDGs as a reference inpreparation of documents National Long-Term Development Plan (RPJPN) 2005-2025. To examine the implementation of the Sustainable Development Goals (SDGs) must be evaluated how the condition of development gains in Medan via indicator Millienium Development Goals (MDGs) that specifically alleviate poverty and hunger (goal 1 MDGs) so it can be recommended several measurement programs that can affect target-setting achievements of Sustainable Development Goals (SDGs) in Medan. Data analysistechniques used to approach the quantitative approach, but in the scope of descriptive analysis by exploring the data in the form of tables and graphs. The results showed that the conditions of development gains in Medan via indicator Millienium Development Goals (MDGs) basically has been running well in which of the seven indicators that proclaimed the majority of activity has been reached.